2020
DOI: 10.1002/hep.31187
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatocellular Carcinoma in the Precision Medicine Era: From Treatment Stage Migration to Therapeutic Hierarchy

Abstract: Treatment allocation is extremely complex in patients with hepatocellular carcinoma (HCC) because this neoplasm arises, in most cases, in patients with cirrhosis and additional comorbidities. The “stage hierarchy” approach, which involves linking each stage (or substage) of the disease to a specific treatment, has become the main proposed treatment strategy for the clinical management of HCC, particularly in the West. The Barcelona Clinic Liver Cancer (BCLC) scheme serves as the main example of the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 49 publications
4
115
0
Order By: Relevance
“…cabozantinib, regorafenib, lenvatinib, ramucirumab and sorafenib) and three kinds of immunotherapy (nivolumab, pembrolizumab and nivolumab plus ipilimumab) have been recommended by NCCN guidelines (version 2020) based on findings from several recent clinical trials. 14 The current challenge is to better A. Each cell of the block contains the pooled HR and 95% credibility intervals for OS and PFS; significant results are in bold.…”
Section: Discussionmentioning
confidence: 99%
“…cabozantinib, regorafenib, lenvatinib, ramucirumab and sorafenib) and three kinds of immunotherapy (nivolumab, pembrolizumab and nivolumab plus ipilimumab) have been recommended by NCCN guidelines (version 2020) based on findings from several recent clinical trials. 14 The current challenge is to better A. Each cell of the block contains the pooled HR and 95% credibility intervals for OS and PFS; significant results are in bold.…”
Section: Discussionmentioning
confidence: 99%
“…Once discovered, a great deal of HCC patients have missed the best opportunity for surgical resection, following that 70% patients undertake recurrence within 5 years . Furthermore, HCC is an aggressive solid tumor easily non-sensitive to chemotherapeutics applied at present 13 . Above all, it's imperative to improve the e cacy for identi cation of novel biomarkers at preliminary stage of HCC and then make therapies for HCC much more costeffective.Located on chromosome 17q21.2 and with a molecular weight of 48 kDa, KRT23 expresses a 1.65 kb mRNA and has been reported to have some function in several cancers.Protein KRT23 was highly upregulated in primary rectal cancer, which was analyzed by immunochemistry 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have also shown superior results for aggressive surgical approach than locoregional therapy in HCC. Therefore, the concept of "treatment stage migration" is emerging with either "left to right" or even "right to left" shift for selection of therapy in the BCLC algorithm (28). This means considering liver resection in patients with either vascular invasion or consideration of liver transplantation in patients with downstaging of tumor with locoregional therapy or outside Milan's criteria (29)(30)(31).…”
Section: Clinical Management Surgical Modalitiesmentioning
confidence: 99%